Kesadaran dan Pandangan Pustakawan terhadap Kesiagaan Bencana Koleksi Digital di Jakarta - Yashodara, Gracia (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2024)
Disaster is an unavoidable event and has the potential to destroy recorded information. Library as an information institution is responsible for preserving all of its collections, including digital collections. Digital collections are collections that require more specialized level of care than physical collections because they require maintenance from both hardware and software. Therefore, digital disaster preparedness is needed to minimize the impact of disasters and build library capabilities that will be needed when disasters come. Librarians need to have a broad view and awareness of the importance of digital disaster preparedness in libraries, especially in university libraries. This research used a quantitative approach with the descriptive analysis method. The result shows that the views of librarians in digital disaster preparedness at university libraries in Jakarta, Indonesia are quite good but there are still a number of things that need to be improved such as a clear written policy to support the ease of flow when dealing with disasters directly. The barriers to digital disaster preparedness encountered by lack of librarians who understand about digital disasters preparedness due to lack of training or further education.